مبدأ عالمية الاختصاص القضائي الجنائي والحصانة الجنائية لرؤساء الدول - Ahmad Abdullah Widan; Al-Saddiq Daww Al-Nur; Abdul Samat Musa (Universiti Sains Islam Malaysia, 2024)
This research aims at studying the international law of criminal justice of national courts and penal immunity of presidents of countries, which allow any countries to practice judgment on specific crimes of international concerns that cannot be detected within limited boundaries. The problem statement of this research is that applying the law of international criminal justice clashes with a number of approved law principles such as sovereignty of all countries, immunity clause in national constitution and international law of the presidents of the respective countries. This research uses analytical method to present a particular legal situation and problems of applying the relevant law. It is found that although the concept of international law of criminal justice is very important due to its principle that any war criminals cannot escape penalty, it is usually difficult to apply it practically because of its clashes with the political motives. It is, therefore, necessary to regulate certain principles in this law to ensure its proper implementation.